Global Exponential Stability of Positive Almost Periodic Solutions for a Fishing Model with a Time-Varying Delay - Hong Zhang; Shuhua Gong; Jianying Shao (Abstract and Applied Analysis)
This paper is concerned with a nonautonomous fishing model with a time-varying delay. Under proper conditions, we employ a novel argument to establish a criterion on the global exponential stability of positive almost periodic solutions of the model with almost periodic coefficients and delays. Moreover, an example and its numerical simulation are given to illustrate the main results.